Health and Nutritional Profile of Working and Non-Working Slum Children (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Background: The nutritional status of children does not only directly reflect the socioeconomic status of the family and social wellbeing of the community, but also the efficiency of the health care system, and the influence of the surrounding environment. Objective: The present study is an attempt to assess the health and nutritional profile of working and non working slum children in selected slum in Dhaka. Methods: It was a cross sectional descriptive study. The subjects were selected purposively. The study was conducted among 200 slum children in three slum area of Dhaka city. Anthropometric data such as height and weight of the study subjects were collected by using standard techniques. Nutritional status was measured according to WHO guideline. Result: Most of children came from around 12 year age group and male, female distribution was equal. Most of them was Muslim and their income was